Factors Related to the Utilization of the National Health Insurance Program (JKN) at Batang Toru Community Health Center, South Tapanuli Regency in 2019 - Siregar, Leli Khairani; Nasution, Sri Lestari Ramadhani; Ginting, Johannes Bastira; Girsang, Ermi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the factors associated with the use of the JKN program, namely individual characteristics (age, education, and employment), capability characteristics (availability of health workers and location accessibility), and characteristics of needs (illness perception). The populations in this study are all people who underwent health services at Batang Toru Health Center in South Tapanuli Regency with a total sample of 98 people. Data were collected using a questionnaire and analyzed using the Pearson Correlation test and multiple logistic regression tests. The results showed that there was a significant relationship with age (p = 0,000); education (p = 0.001); occupation (p = 0,000); availability of health workers (p = 0,000); location accessibility (p = 0,000) and pain perception (p = 0, 000) with the use of the JKN program at Batang Toru Health Center. The results of paper multivariate analysis and modeling showed that the factors that were significantly and dominantly related to the use of the JKN program at Batang Toru Health Center were the availability of health workers, location accessibility factors, and illness perception factors. Thus it was concluded that the availability of health workers, accessibility of location, and perception of pain were significantly and dominantly related to the use of the National Health Insurance (JKN) program at Batang Toru Health Center in South Tapanuli Regency in 2019 of health workers is the most dominant factor and has the biggest influence on the use of the JKN program location accessibility factors and illness perception factors. Â